Pengaruh Kesadaran Diri, Kestabilan Emosi, dan Lingkungan Belajar terhadap Motivasi Belajar Siswa di SMA Muhammadiyah - Anisha Nurul Fatimah; Muhammad Wildan Shohib; Hamdan Chehdimae (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The motivation of students at Muhammadiyah Senior High School Pondok Pesantren Modern Imam Syuhodo has become a concern because there are still students who face difficulties in maintaining their learning enthusiasm. Several factors are suspected to influence the low motivation of students, including a lack of self-awareness in managing time and learning responsibilities, emotional stability affecting academic focus, and a learning environment that is not yet fully conducive. The personality of students, particularly in terms of self-awareness and emotional stability, plays a crucial role in determining how they face academic challenges. In addition, the learning environment, both inside and outside the school, can influence students' motivation to achieve better academic results. This study aims to analyze the impact of self-awareness, emotional stability, and the learning environment on students' learning motivation at Muhammadiyah Senior High School Pondok Pesantren Modern Imam Syuhodo. The method used in this study is a quantitative survey, with data collected through questionnaires involving 200 students. Data analysis using Smart PLS shows that self-awareness, emotional stability, and the learning environment have a significant and positive impact on students' learning motivation. These findings emphasize that internal factors, such as self-awareness and emotional stability, as well as external factors, such as the learning environment, significantly influence students' learning motivation. Therefore, the findings of this study highlight the importance of developing these two factors and suggest that more attention be given to these aspects to maximize students' potential in the learning process and their academic achievements.